Ketahanan Keluarga di Era Digital: Tantangan Privasi, Pola Asuh, dan Ketergantungan Media Sosial (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2025)
This study explores the resilience of families in the digital era, focusing on three major challenges: digital privacy, parenting transformation, and social media dependency. Using a qualitative descriptive approach through literature review, the research analyzes various scholarly sources, including national and international journals, official statistical data, and relevant theoretical frameworks. The findings indicate that digital privacy is often compromised due to the family's lack of digital literacy, particularly in managing social media usage and data sharing habits. Additionally, parenting patterns have shifted from conventional authority-based models to more collaborative and digital-aware approaches, commonly referred to as "digital parenting." Parents are now expected to engage actively in their children's online experiences rather than serving solely as supervisors. Moreover, social media dependency has emerged as a major disruptor of family harmony, reducing face-to-face communication, empathy, and emotional connection between family members. This condition threatens the core values of familial unity. To counter these challenges, the study recommends a combination of digital education, value-based parenting, communication revitalization, and the establishment of healthy digital boundaries at home. By integrating technology with ethical and spiritual guidance, families can maintain emotional cohesion and remain resilient amidst the pressures of modern digital life.